The Implementation of Wi-Fi Network Security System in Bukit Peninjauan II Village - Taufik Hidayat; Khairil Khairil; Deri Lianda (CV. Generasi Insan Rafflesia, 2026)
Public Wi-Fi networks are highly vulnerable to the misuse of Internet access, particularly for accessing websites containing online gambling, pornographic content, and illegal online lending services. Similar issues were identified in the public Wi-Fi network of Bukit Peninjauan II Village, which lacked an effective website filtering mechanism. This study aims to implement a network security system using MikroTik firewall integrated with DNS Static based on Regular Expressions (Regex), TLS Host Filtering, and the blocking of DNS over HTTPS (DoH) and QUIC protocols. This study used the Network Development Life Cycle (NDLC) methodology, which consists of the analysis, design, implementation, testing, and evaluation phases. The proposed system was implemented on the public Wi-Fi network of Bukit Peninjauan II Village by configuring firewall rules to filter website access based on predefined domain patterns. The results demonstrate that the implemented Firewall Filter, DNS Static Regex, TLS Host Filtering, DNS over HTTPS (DoH) blocking, and QUIC blocking functioned as intended. The system successfully restricted access to websites related to online gambling, pornographic content, and illegal online lending services without affecting access to authorized websites. Furthermore, blocking DoH and QUIC effectively prevented users from bypassing the implemented filtering mechanism. In conclusion, the proposed network security system effectively enhances Internet access control and provides a safer, more secure, and better-managed public Wi-Fi environment for the community of Bukit Peninjauan II Village.